ACADEMIC, PERSONAL AND INSTITUTIONAL PREDICTORS OF JOB READINESS : AN INSIGHT FROM RECENT COHORT UNIVERSITY GRADUATES - Ana Noveria (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The research seeks to explain the impact of academic achievements, personal competencies, institutional features, teaching and learning method and personal development on graduates’ job readiness under the current economic situation. The dramatic changes in unemployment of youth (under 24 of age) started a new debate on the relevance and acquisition of employer-specific skills and competencies obtained from higher education institutions. Following the quantitative approach, data from 611 students who graduated in 2020 and surveyed in 2022 from a public university located in the West Java province of Indonesia, structural equation modeling (SEM) technique, the study evaluates the role and relevance of different skills and competencies obtained from a higher education institution for seeking formal employment. The findings indicate that academic achievements, personal competencies, institutional features and learning and teaching are significant whereas personal development are insignificant contributors to graduates’ job readiness. The results also confirm a significant positive moderating impact of financial support in improving academic achievements, personal competencies and teaching and learning of graduates seeking formal employment. Similarly, the moderating results of job market conditions highlighted as one of the key contributors to pushing graduates to focus on academic excellence, personal competencies and development.